Researching basic searchable encryption schemes in databases that support SQL - Yesin, V.I.; Vilihura, V.V. (Radiotekhnika, 2022)
Currently, many users prefer to outsource data to third-party cloud servers in order to mitigate the load of local storage. However, storing sensitive data on remote servers creates security challenges and is a source of concern for data owners. With ever-growing security and privacy concerns, it is becoming increasingly important to encrypt data stored remotely. However, the use of traditional encryption prevents the search operation in the encrypted data. One approach to solving this problem is searchable encryption. Solutions for search in secure databases cover a wide range of cryptographic techniques, although there is still no dominant solution. Designing secure search systems is a balance between security, functionality, performance, and usability. Therefore, this paper provides an overview of some of the important current secure search solutions. The main searchable encryption systems of databases that support SQL are considered. The strengths and weaknesses of the analyzed systems and the techniques implemented in them are highlighted. A comparative analysis of some characteristics of the compared systems is given. Attention is drawn to the fact that the ability to perform search operations in encrypted data leads to a complication of systems, an increase in the amount of required memory and query execution time. All this indicates the openness of the protected search problem and the need for further research in this direction to ensure secure work with remote databases and data warehouses.